Hypothalamic peroxisome proliferator-activated receptor gamma regulates ghrelin production and food intake. (June 2018) - Li, Qingjie; Yu, Quan; Lin, Li; Zhang, Heng; Peng, Miao; Jing, Chunxia; Xu, Geyang
Abstract: Peroxisome proliferator-activated receptor-γ (PPARγ) regulates fatty acid storage, glucose metabolism, and food intake. Ghrelin, a gastric hormone, provides a hunger signal to the central nervous system to stimulate appetite. However, the effects of PPARγ on ghrelin production are still unclear. In the present study, the effects of PPARγ on ghrelin production were examined in lean- or high-fat diet-induced obese (DIO) C57BL/6J mice and mHypoE-42 cells, a hypothalamic cell line. 3rd intracerebroventricular injection of adenoviral-directed overexpression of PPARγ (Ad-PPARγ) reduced hypothalamic and plasma ghrelin, food intake in both lean C57BL/6J mice and diet-induced obese mice. These changes were associated with a significant increase in mechanistic target of rapamycin complex 1 (mTORC1) activity. Overexpression of PPARγ enhanced mTORC1 signaling and suppressed ghrelin production in cultured mHypoE-42 cells. Our results suggest that hypothalamic PPARγ plays a vital role in ghrelin production and food intake in mice. Highlights: Intracerebroventricular injection of Ad-PPARγ activates hypothalamic mTOR signaling in lean and obese mice. Infusion of Ad-PPARγ decreases hypothalamic ghrelin mRNA and protein levels, as well as circulating ghrelin in mice. Central administration of Ad-PPARγ suppresses food intake in mice. Overexpression of PPARγ stimulates mTORC1 activity while it inhibits ghrelin production in mHypoE-42 cells.